A revisit on the compactness of commutators - Guo, Weichao; Wu, Huoxiong; Yang, Dongyong (Canadian journal of mathematics, 2021)
A new characterization of $\text {CMO}(\mathbb R^n)$ is established replying upon local mean oscillations. Some characterizations of iterated compact commutators on weighted Lebesgue spaces are given, which are new even in the unweighted setting for the first order commutators.